2022
DOI: 10.1038/s41416-022-02082-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of radiation therapy in advanced adrenocortical carcinoma

Abstract: Background International guidelines emphasise the role of radiotherapy (RT) for the management of advanced adrenocortical carcinoma (ACC). However, the evidence for this recommendation is very low. Methods We retrospectively analysed all patients who received RT for advanced ACC in five European centres since 2000. Primary endpoint: time to progression of the treated lesion (tTTP). Secondary endpoints: best objective response, progression-free survival (PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In our study with 80 patients, we reported 43 grade 1 adverse events including fatigue, anaemia, skin, hepatic, renal, intestinal, and pulmonary toxicities. In addition, we observed 13 grade 2 adverse events with fatigue, musculoskeletal disorders, skin, pulmonary, and intestinal toxicities, and three grade 3 adverse events (with pulmonary and intestinal toxicities) (26). Both of these studies reported no grade 4 or 5 adverse events.…”
Section: Radiotherapymentioning
confidence: 57%
See 2 more Smart Citations
“…In our study with 80 patients, we reported 43 grade 1 adverse events including fatigue, anaemia, skin, hepatic, renal, intestinal, and pulmonary toxicities. In addition, we observed 13 grade 2 adverse events with fatigue, musculoskeletal disorders, skin, pulmonary, and intestinal toxicities, and three grade 3 adverse events (with pulmonary and intestinal toxicities) (26). Both of these studies reported no grade 4 or 5 adverse events.…”
Section: Radiotherapymentioning
confidence: 57%
“…Thus, we conclude that RT seems to be mostly well-tolerated and effective in the management of metastatic ACC, controlling local symptoms, and preventing complications from large metastases. More recent data clearly suggest that higher radiation dosages (e. g., > 50 Gy) or stereotactic body radiotherapy might -not surprisingly -be more effective in achieving objective tumour response [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy plays an increasing role in the treatment of ACC. It can be beneficial both adjuvantly, in patients at high risk of recurrence [19], but also in the management of metastases [20][21][22]. Radiotherapy is therefore recommended by current guidelines for the control of imminent complications or oligometastatic disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…The manuscripts by Kimpel et al [7] and Schwarzlmueller et al [8] complement each other in underscoring the utility of localized treatment in metastatic adrenocortical carcinoma (ACC). While firm conclusions on some modalities are hampered by the heterogeneity of local practice and expertise, it appears that radiotherapy may be particularly useful for local control of ACC.…”
Section: Germany Nicolebechmann@ukdddementioning
confidence: 99%